Does Community Affluence Improve Survival of Colorectal Cancer? - Barbara Nemesure, PhD; Linda K. Mermelstein, MD, MPH; Kathleen H. Scarbrough, MD, MPH (AJPM Focus, 2023)
Introduction: Colorectal cancer is the second most common cause of cancer-related death in the U.S. Lower SES and lack of health insurance coverage are 2 known risk factors for lower colorectal cancer survival. The primary objective of this research is to evaluate the survival rates of patients diagnosed with colorectal cancer who reside in an affluent suburb and to examine factors that may impact mortality. Methods: Information was collected from the Stony Brook Cancer Center registry for all cases of colorectal cancer diagnosed between 2010 and 2020. The Distressed Community Index, a proxy for SES based on geographic location and data obtained from the U.S. Census, was paired with patient ZIP codes to evaluate the impact of prosperity on survival. Chi-square tests, Kaplan–Meier survival curves, and hazard ratios are presented. Results: Among 946 patients with colorectal cancer, more than half resided in a prosperous (Distressed Community Index ≤20) ZIP code. Age and sex were similar between Distressed Community Index groups; however, a significant association was found between Black race and Distressed Community Index score >20 (p<0.01). Patients who were married were more likely to live in a prosperous ZIP code (p<0.01), whereas those with Medicaid health insurance were more likely to reside in a nonprosperous community (p<0.01). More than 75% of cases were diagnosed at Stage 2 or higher, and survival rates at 1 year and 5 years were 84.6% and 59.2%, respectively. Stage at diagnosis and overall survival were not associated with Distressed Community Index status. Older age (≥70 years) (hazard ratio=2.43, 95% CI=1.18, 5.01) and late stage at diagnosis (hazard ratio= 12.24, 95% CI=6.86, 21.81) were found to be associated with increased mortality at 5 years. Conclusions: In this relatively affluent study population from a tertiary care facility registry, improved survival rates among patients with colorectal cancer were not observed compared with national averages. Advanced stage of diagnosis and older age increased mortality in persons with colorectal cancer. Because early detection remains one of the most important tools for improving survival outcomes, efforts to increase screening education and reduce barriers as well as address challenges with screening adherence would likely benefit the population at risk, irrespective of community prosperity.